IMPLEMENTATION OF PUBLIC SERVICE REFORM IN ENHANCING THE WELFARE OF BIMA DISTRICT COMMUNITY: CHALLENGES AND OPPORTUNITIES - Satika, Renni; Salahuddin; Kasman; Suraya (KOMUNITAS, 2024)
This study examines the implementation of public service reforms in Bima District with the goal of enhancing community welfare. Utilizing a qualitative and descriptive approach, primary data were gathered through in-depth interviews with local stakeholders, while secondary data were sourced from policy documents and statistical reports. Thematic analysis was employed to categorize findings based on research objectives. Results show positive changes like improved health service accessibility and quality. However, challenges persist in management, service standards compliance, and policy alignment with community needs due to bureaucratic rigidity and lacking leadership. The research concludes that while reforms have benefits, there's substantial room for improvement, particularly in management, transparency, and service delivery innovation. It emphasizes the need for strong commitment across government levels to drive innovation, address infrastructure and human resource barriers, and enhance institutional coordination, thereby directly impacting community welfare in Bima District.